Ethical challenges of artificial intelligence: introduction - Kučera, Dušan (Henry Stewart Talks, 2020)
Definition of ethics, Definition of management, The 4 industrial revolutions, Definition of Artificial Intelligence, Optimism and expectations, Warnings, Ethical challenges, VW emission scandal